2020
DOI: 10.1186/s12906-020-03067-3
|View full text |Cite
|
Sign up to set email alerts
|

NMR and LCMS analytical platforms exhibited the nephroprotective effect of Clinacanthus nutans in cisplatin-induced nephrotoxicity in the in vitro condition

Abstract: Background Clinacanthus nutans (C. nutans) Lind. locally known as Belalai Gajah or Sabah snake grass is a medicinal plant belonging to Acanthaceae family. In Asia, this plant is traditionally used for treating skin rashes, insects and snake bites, diabetes mellitus, fever and for diuretic effect. C. nutans has been reported to possess biological activities including anti-oxidant, anti-inflammation, anti-cancer, anti-diabetic and anti-viral activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Additionally, Gilda et al [18] identified 35 metabolites, along with antioxidant and AG inhibitory effects of the fruits of both Morus alba and Morus nigra. Similar technology has been applied to evaluate the activity of Clinacanthus nutans leaves against cisplatin toxicity [19]. In addition, potential thrombin/factor Xa inhibitors were reported from Salvia miltiorrhiza Bunge and Ligusticum chuanxiong Hort using the LC-MS-based multivariate data analysis technique [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Gilda et al [18] identified 35 metabolites, along with antioxidant and AG inhibitory effects of the fruits of both Morus alba and Morus nigra. Similar technology has been applied to evaluate the activity of Clinacanthus nutans leaves against cisplatin toxicity [19]. In addition, potential thrombin/factor Xa inhibitors were reported from Salvia miltiorrhiza Bunge and Ligusticum chuanxiong Hort using the LC-MS-based multivariate data analysis technique [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…C. nutans has also been evaluated for its renoprotective activities. The renoprotective effect of C. nutans has been demonstrated by several in-vivo and in-vitro studies [ 63 , 64 , 65 ]. In 2017, the nephroprotective effect of C. nutans leaves against cisplatin-induced nephrotoxicity and the safety assessment of C. nutans leaves has been demonstrated by [ 63 ].…”
Section: Pharmacological and Medicinal Propertiesmentioning
confidence: 99%
“…Collectively, these findings highlighted the potential use of C. nutans leaves extract in the management and treatment of cisplatin-induced nephrotoxicity. Meanwhile, [ 64 ] has also reported the nephroprotective effect of C. nutans in cisplatin-induced nephrotoxicity under an in-vitro condition using the Proton Nuclear Magnetic Resonance ( 1 H NMR) and Liquid Chromatography Mass Spectroscopy (LCMS) techniques coupled with multivariate data analysis to characterize the metabolic variations in intracellular metabolites and the compositional changes of the corresponding culture media in rat renal proximal tubular cells (NRK-52E). Investigations of this study have highlighted the altered pathways perturbed by cisplatin induced nephrotoxic on NRK-52E cells which involved changes in amino acid metabolism, lipid metabolism and glycolysis such that choline, creatinine, phosphocholine, valine, acetic acid, phenylalanine, leucine, glutamic acid, threonine, uridine and proline as the main metabolites which differentiated the cisplatin induced group of NRK-52E from control cells extract while the corresponding media exhibited lactic acid, glutamine, glutamic acid and glucose-1-phosphate as the varied metabolites.…”
Section: Pharmacological and Medicinal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, C. nutans contains sulfur‐containing compounds, which have been reported to possess antioxidant and anti‐inflammatory properties (Khoo et al, 2019). Our group has recently demonstrated the potential nephroprotective effect of C. nutans aqueous extract (1000 μg/mL) against cisplatin‐induced nephrotoxicity in renal proximal tubular cells (NRK‐52E) of rat at 89% cell viability (Mahmod et al, 2020). This has piqued our interest in delving deeper into the nephroprotective potential of C. nutans extracts on human kidney cells (PCS‐400‐010).…”
Section: Introductionmentioning
confidence: 99%